The Influence of Id, Ego, and Superego on Love and Sacrifice in Katniss Everdeen and Peeta Mellark’s Relationship in The Hunger Games - Fidela Larissa Evelina Valda (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
The purpose of this study is to examine how Sigmund Freud's psychological structures—the id, ego, and superego—affect how love and sacrifice are portrayed in Katniss Everdeen and Peeta Mellark's relationship in Suzanne Collins' novel The Hunger Games. While psychoanalytic studies have concentrated more on the psychological problems of particular characters, previous research on this novel has typically centered on themes of dystopia, power, socio-political criticism, and survival techniques. Therefore, by investigating how Freud's personality structures interact with the dynamics of love and sacrifice in the two major characters' relationship, this study closes the research gap. The connection between Katniss Everdeen and Peeta Mellark as it is portrayed in the story, language, ideas, and deeds of the characters in the book is the subject of the study. This study combines a literary psychoanalytic viewpoint with a qualitative descriptive methodology. Freud's theory of personality structures, which includes the id, ego, and superego, was used to assess the data that was gathered using close reading methods and document analysis. The findings demonstrate how love in Katniss and Peeta's relationship arises from emotional dependence, protection, and caring in the face of harsh circumstances. Emotional drives and affective needs (id), logical assessments of reality and survival tactics (ego), and moral principles, empathy, and obligation to others (superego) all have an impact on their sacrifices. The results of the study also show that acts of love and sacrifice are produced by the dynamic interaction of the id, ego, and superego, which influence one another during the decision-making process rather than by a single personality structure acting individually. By showing that interpersonal connections in literary works can be comprehended through the intricate interaction of instinctual urges, logical considerations, and moral standards that determine character conduct, this research has implications for the advancement of literary psychoanalysis.